Al Ghathami’s الثقافة التلفزیونیة - Television Culture (2005): Translation and a Skoposbased Commentary - Al-Ali, Hamad M. (2022)
A Master of Arts thesis in English/Arabic/English Translation and Interpreting (MATI) by Hamad M. Al-Ali entitled, “Al Ghathami’s الثقافة التلفزیونیة - Television Culture (2005): Translation and a Skoposbased Commentary”, submitted in April 2022. Thesis advisor is Dr. David Wilmsen. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).